Do Better Customers Utilize Electronic Distribution Channels? The Case of PC Banking - Hitt, Lorin M.; Frei, Frances X. (Management Science, 2002)
Many service firms are pursuing electronic distribution strategies to augment existing physical infrastructure for product and service delivery. But little systematic study has been made for whether and how characteristics or behaviors might differ between customers who use electronic delivery systems and those who use traditional channels. We explore these differences by comparing customers who utilize personal-computer-based home banking (PC banking) to other bank customers. Case studies and detailed customer data from four institutions suggest that PC banking customers are apparently more profitable, principally due to unobservable characteristics extant before the adoption of PC banking. Demographic characteristics and changes in customer behavior following adoption of PC banking account for only a small fraction of overall differences. It also appears that retention is marginally higher for customers of the online channel.